Relevant aspects of propagating a combustion front in an annular reactor for out-of-bed heat recovery - Duque, João Vitor F.; Martins, Márcio F.; Bittencourt, Flávio L.F.; Debenest, Gérald (Experimental thermal and fluid science, 2022)
This work investigates for the first time the classical aspects of smoldering front propagation in an annular reactor while presenting new concepts and making new contributions in methodologies of establishing the longitudinal temperature profile, calculating the front velocity, and determining the combustion front’s regime. Twenty-nine experiments using different porous beds supported the argument that annular reactor design is, at present, the best for recovering the combustion heat for concomitant processes. Three methods for calculating the front velocity were employed, of which the mass derivative and mass balance methods were specially developed for combustion in heterogeneous beds. The mass balance modeling constrained by the gas analysis results revealed the reactions’ stoichiometry and front velocity relationships with the product formation rate. As a result, the model returned the total oxygen mass, front velocity correction, actual fixed carbon amount oxidized by the front, and the Equivalent Ratio (ER) value, a concept borrowed from gasification studies. It was found that the smoldering front propagated under a gasification regime 0.21 ¡ ER ¡ 0.37. The front structure revealed that the oxidation reaction’s heat was mostly convected downstream of the reaction front resulting in an average bed temperature increase even when the front was close to its propagation’s limit. Finally, the Energy Availability (EA) assessment confirmed that the smoldering front propagation in an annular section is one exceptional design to drive the energy out-of-bed to feed a concomitant process — considering a pyrolysis heat of 1100 kJ/kg for the study. [Display omitted] •Smoldering front propagation in a reactor with annular cross-section.•New reactor design, Combustion Driven Pyrolysis Reactor, C-DPyR.•Out-of-bed heat recovering for concomitant processes.•High energy availability allows the conversion of energy-intensive materials.•Feasibility of using low-grade fuels to drive heat.